Au-pair: Von der Kulturträgerin zum Dienstmädchen Die moderne Kleinfamilie als Bildungsbörse und Arbeitsplatz - Orthofer, Maria (2008)
Since the 1970s, highly educated families in Austria have employed Au-pairs for taking care of their children. Why have these families preferred Au-pairs to kindergartens with qualified teachers? Were Au-pairs just a flexible substitute or did they have additional functions in the family? Which social and political climate has favoured this private form of childcare? The empirical basis of the work was the documentation of one of the major Austrian Au-pair agencies for the period 1978 - 2000, particularly 298 self-descriptions from guest families and the agency´s annual reports. The material was supplemented by interviews with ten guest families and by interviews with two experts. Thus is possible to analyze the socio-demographic characteristics of guest-families in Vienna and its suburbs, their motivations for taking Au-pairs, and their expectations. The findings indicate that Au-pairs usually serve several roles within the families: for instance, one very important role is to "double" mothers in order to free their minds to continue their social and work life. The pair system is also discussed in view of its two historic threads: one is a long European "education abroad" tradition for rather upper class children. The other thread is a "work-migration" tradition for lower class childs that had to go to cities to work as domestic servants. Which of the two traditions dominates the Au-pair market depends on the economic situation of the countries from which the Au-pairs come. Consequently, the economic and political changes around 1989 in Eastern Europe have had major impacts on the characteristics of Au-pair jobs in Austria